Product Life Cycle Management in Industry 4.0 (AACINI - International Journal of Industrial Engineering, 2021)
Market demand is changing, which results in the reconfiguration of the value chains of suppliers, companies and clients. Companies seek to differentiate themselves by adding value to their products and services. Smart products, from their conception to their removal or reuse, are a key piece in this new industrial revolution. Industry 4.0 allows an end-to-end management, from the survey of customer requirements, to reuse or recycling. Managing product life cycle information provides answers to the current demand needs and improves business performance. For this, Industry 4.0 can achieve, among other challenges, the convergence between Information Technology Systems and Operational Technology Systems. During this this work, scientific articles and the IEC 62.890 and IEC 62.264 standards were studied. The main objective of the study was to propose an additional phase to the Value Flow Life Cycle of the Industry 4.0 Reference Architecture Model, combining it with both horizontal and vertical integration. It is proposed, for future research, its validation through a practical case of digitization of products and the core process of a company.
Keywords: Industry 4.0; Product life cycle; Value stream; RAMI 4.0; Samrt product